(untitled) (International Journal of Environmental Sciences, 2024)
Patient safety is a critical priority in healthcare systems, and leadership practices play an important role in shaping safety culture and improving the quality of patient care. This study examines the influence of two transformational leadership dimensions intellectual stimulation and individualized consideration on patient safety outcomes among nurses at King Faisal Specialist Hospital in Riyadh, Saudi Arabia. A quantitative cross-sectional research design was employed to investigate the relationships between these leadership behaviors and patient safety outcomes. Data were collected using a structured questionnaire distributed to nurses working in the hospital, and a total of 109 valid responses were obtained for statistical analysis. The study measured intellectual stimulation, individualized consideration, and patient safety outcomes using a five-point Likert scale. Reliability and validity tests were conducted to ensure the consistency of the measurement scales, followed by descriptive statistics, correlation analysis, and multiple regression analysis to examine the relationships among the variables. The results indicate that individualized consideration has a significant positive influence on patient safety outcomes, suggesting that supportive leadership behaviors that focus on the individual needs and development of nurses contribute to improved safety practices. In contrast, intellectual stimulation did not demonstrate a statistically significant effect on patient safety outcomes in this context. These findings highlight the importance of supportive leadership approaches in healthcare environments and suggest that leadership behaviors emphasizing mentorship, guidance, and staff support can enhance patient safety practices. The study provides valuable insights for healthcare leaders and hospital administrators seeking to strengthen patient safety culture and improve the quality of care delivered in clinical settings.